A novel double‐doped polymer‐modified cement‐based sealant to enhance borehole seals and reduce methane emissions. Issue 2 (11th February 2020) - Zhou, Aitao; Wang, Jiawen; Wang, Kai; Elsworth, Derek; Zhang, Meng
Abstract: This study was conducted to develop a new type of sealing material: double‐doped polymer‐modified cement‐based sealant (DPCS) and to verify its sealing performance. The aim is to improve the sealing effect of borehole, improve the gas extraction efficiency, and reduce methane emissions. Two kinds of polymers are doped in DPCS, namely the water‐soluble polymer emulsion (A1) and the cationic polymer (A2). The fluidity, expansion, compactness, and mechanical properties of DPCS and the single‐doped polymer‐modified sealant were tested and compared. Additionally, the effects of the polymer–cement ratio and the dispersant dosage on the sealing performance of DPCS were analyzed. To evaluate these competing effects of multiple factors on sealing performance of DPCS comprehensively, an orthogonal test was designed with range and variance analyses. The results show that with a polymer–cement ratio of 6%, 0.10% expansion agent dosage, and 1.2% dispersant dosage, the DPCS performs best on mechanical and expansion properties. A field site test at the working face 15201 of the Baiyangling coal mine was conducted to verify DPCS's sealing performance. The test results indicate that the novel DPCS can improve the concentration of extracted gas, and is also a better choice than the common sealing materials used in the mine economically. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.